Prior Hospitalization and the Risk of Heart Attack in Older Adults: A 12-Year Prospective Study of Medicare Beneficiaries - Wolinsky, Fredric D. (Oxford University Press, 2010)
BACKGROUND. We investigated whether prior hospitalization was a risk factor for heart attacks among older adults in the survey on Assets and Health Dynamics among the Oldest Old. METHODS. Baseline (1993–1994) interview data were linked to 1993–2005 Medicare claims for 5,511 self-respondents aged 70 years and older and not enrolled in managed Medicare. Primary hospital International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) 410.xx discharge codes identified postbaseline hospitalizations for acute myocardial infarctions (AMIs). Participants were censored at death or postbaseline managed Medicare enrollment. Traditional risk factors and other covariates were included. Recent postbaseline non-AMI hospitalizations (ie, prior hospitalizations) were indicated by a time-dependent marker, and sensitivity analyses identified their peak effect. RESULTS. The total number of person-years of surveillance was 44,740 with a mean of 8.1 (median = 9.1) per person. Overall, 483 participants (8.8%) suffered postbaseline heart attacks, with 423 participants (7.7%) having their first-ever AMI. As expected, significant traditional risk factors were sex (men); race (whites); marital status (never being married); education (noncollege); geography (living in the South); and reporting a baseline history of angina, arthritis, diabetes, and heart disease. Risk factors were similar for both any postbaseline and first-ever postbaseline AMI analyses. The time-dependent recent non-AMI hospitalization marker did not alter the effects of the traditional risk factors but increased AMI risk by 366% (adjusted hazards ratio = 4.66, p < .0001). DISCUSSION. Our results suggest that some small percentage (<3%) of heart attacks among older adults might be prevented if effective short-term postdischarge planning and monitoring interventions were developed and implemented.